Analisis Perubahan Faktor Keamanan Lereng Akibat Hujan - Achmad Hafidz; Muhammad Fauzan; Heriansyah Putra; Annisa Daniswara (Departemen Teknik Sipil dan Lingkungan, IPB University, 2019)
Infiltration causes a decrease in soil shear strength parameters. Decrease in soil shear strength parameters can cause landslides. Landslides often occur in Bogor Regency, one of the landslide locations is Puncak, Bogor. Landslides in Puncak, Bogor on 05 February 2018 at 09.20 WIB must have a safety factor 1.07. Changes in safety factors due to rainfall are observed from 03 February 2018 at 05.00 WIB until 05 February 2018 at 09.20 WIB. This research includes testing soil samples, pore water pressure analysis and slope stability analysis. The software used for this analysis is GeoStudio. The analysis results are the changes in safety factor due to rainfall. The safety factor on 03 February 2018 at 05.00 WIB is 1.602. Safety factor until 05 February 2018 at 03.40 WIB are still above 1.25. So, the slopes are still safe. The decline in safety factor continued until 1.070 due to a decrease in cohesion on 05 February 2018 at 09.20 WIB with cohesion on SW-SM soil and SM soil at 4.01 kPa and 9.18 kPa. So, the duration needed to change a safe slope to landslide is only 5 hours 40 minutes. This can occur because of the intensity of the rain on 05 February 2018 at 07.00 WIB and 08.00 WIB are 34.1 mm/hour and 34.9 mm/hour. Key words: cohesion, landslides, rainfall, safety factor